EFFECT OF FISH PROTEIN HYDROLYSATE ON GROWTH, YIELD AND STORABILITY OF SOME FEMALE CUCUMBER HYBRIDS (Cucumis Sativus L) GROWN IN PLASTIC HOUSE IN BASRA - Hassan , Mohammed Khazal; Al-Maliki , Abdul Hussein Qasim; Hamza, Hamza Abbas (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
General Background: Cucumber (Cucumis sativus L.) is a widely cultivated vegetable, valued for its nutritional and economic significance. Specific Background: The application of biostimulants, such as fish protein hydrolysate, has gained attention for enhancing plant growth and yield. However, the impact of varying concentrations of fish protein hydrolysate on different cucumber hybrids remains underexplored. Knowledge Gap: Despite existing research on biostimulants, the specific effects of fish protein hydrolysate on hybrid cucumber performance, particularly in unheated plastic houses, are inadequately documented. Aims: This study aimed to evaluate the effects of different concentrations of fish protein hydrolysate on the growth and yield of three cucumber hybrids (